Efektivitas Senam Zumba Terhadap Perubahan Berat Badan Pada Wanita - Anggraini, Rara; Widodo, Achmad (Kesehatan Olahraga, 2022)
The study aims to determine the impact of Zumba on the female body weight of the members os SS Eny Aerobic in Bankalan, Madura. The independent variable used were zumba while the dependent variables subcutaneous fat and body weight. The research method used is a quasi experimental design with one group pre-test post-test design. The population of the study was 15 members of SS Eny Aerobic, the sample used was 15 members. The treatment of the Zumba exercise program was 16 meetings with a frequency of 3 times a week with moderate to higt intemsity. Data retrievel using measurements with Skinfold for the Subcutaneous fat, as well as weight scales for the weight variable. The data analysis technique used T test analysis, through the prerequisite test for normality, and homogeneity. The results showed that there was a significant impact of Zumba on the weight loss of SS Eny Aerobic members. Keywords:Zumba, Weight Loss